Ce-Mn mixed oxides as supports of copper- and nickel-based catalysts for water-gas shift reaction - Poggio Fraccari, Eduardo Arístides (2014)
Cerium-manganese mixed oxides with different composition were prepared by co-precipitation, characterized and evaluated for the water–gas shift (WGS) reaction. Base metal (5 wt.% Cu and 5 wt.% Ni) catalysts supported on Ce–Mn mixed oxides were also tested for the WGS reaction. The activity of the bare supports is higher in the mixed samples than in pure ceria or manganese oxide. This result can be explained by a combination of greater reducibility and surface area in the mixed samples. Addition of base metals produces superior WGS catalysts. Particularly, nickel catalysts tested are able to reduce typical CO concentrations entering the WGS process to the CO levels tolerated by phosphoric acid fuel cells in a single unit operated at 400 °C.